Pengaruh Kesadaran Wajib Pajak, Pengetahuan Perpajakan dan Tingkat Pendidikan terhadap Kepatuhan Wajib Pajak Pada UMKM Di Kota Solok - Aziyah, Herlina; Djefris, Dedy; Andriani, Wiwik (Universitas Batanghari Jambi, 2025)
This study is motivated by the limited research on the factors influencing tax compliance among Micro, Small, and Medium Enterprises (MSMEs), despite the significant impact of this phenomenon on state tax revenues and regional development sustainability. The purpose of this study is to analyze the influence of taxpayer awareness, tax knowledge, and education level on taxpayer compliance among MSME actors in Solok City. This research employed a quantitative approach with a survey design involving 365 MSME actors selected using purposive sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26. The results revealed that taxpayer awareness and tax knowledge had a significant positive effect on taxpayer compliance, while education level had a significant negative effect on compliance. These findings are consistent with the Theory of Planned Behavior, which emphasizes the role of awareness and understanding in shaping compliance behavior, yet they also open new discussions on the role of education in tax compliance. The main conclusion of this study is the importance of enhancing awareness and understanding of taxation for MSME actors as a strategy to increase tax compliance. The implications of this research include theoretical contributions by enriching the literature on MSME taxpayer compliance and practical recommendations for the government and tax authorities to strengthen more targeted tax socialization and education programs. This study also opens opportunities for further research to explore other variables such as tax fairness perception, sanctions, and administrative convenience.